Nutrigenomics: a survey on continuing education needs of registered dietitians in Malaysia - J. M., Hamid Jan; M. J., Siti Norsyaza; Y. H., Tan; Laura I., Bouwman (Nutrition Society of Malaysia, 2008)
Nutrigenomics or diet-gene interactions have become the focus of much nutritional research in recent years. However, little is known about Malaysian dietitians’ involvement and education needs regarding nutrigenomics. The aim of this survey was to assess the awareness and continuing education needs for registered dietitians regarding nutrigenomics. A validated questionnaire was developed to assess involvement, knowledge, chances, barriers and continuing education needs on nutrigenomics among Malaysian dietitians. The questionnaire was distributed to all (n=90) registered dietitians who attended the Malaysian Dietitians’ Association Scientific Conference in year 2007 which resulted in a 46% response rate (n=41). The majority of the respondents (91.5%) graduated from local universities between the years 1988 to 2007. All respondents used information on dietary pattern, lifestyle and body mass index for composing dietary advice. For the same purpose, a high percentage of respondents (91.4%) used family history but only two respondents (5.7%) experienced relying on genetic tests. Although 85.7% of respondents are aware of nutrigenomics, only 22.3% understood its definition. More than 80% of dietitians are interested in learning and increase their knowledge on human genetics, nutrigenomics and ways to communicate this knowledge to the public. Three highest barriers to the application of nutrigenomics are lack of patient education materials (91.5%), lack of background knowledge among dietitians (85.7%) and lack of continuing education for dietitians (80%). The most preferred learning activity for continuing education was seminars. This survey revealed great interest among dietitians to increase and update their knowledge on nutrigenomics. There is a need to include genetics and nutrigenomics knowledge in the continuing education programmes for dietitians in Malaysia. This may help dietitians to make informed decision about the possible use of nutrigenomics in their practice.